University students’ ambition levels and vocational tendencies associated with common culture - H. A. Danaa; M. M. Al-mzary; W. N. Halasa; L. M. Obeidat; M. A. Rababah; M. Kh. Al-Alawneh (Образование и наука)
Introduction. Jordanian education system encourages students to invest their potentials to fulfill their needs, make their ambitions come true and achieve success in their lives. However, many students still face problems in determining their ambitions and vocational tendencies to attain their goals.Aim. This study aims to identify the degree of ambition level and its relation to the vocational tendencies among university students with respect to the common culture. It focused on two main domains, namely the ambition level and its relation with vocational tendencies.Methodology and research methods. A quantitative method was adopted to analyse the data. The study sample consisted of 500 male and female students studying at Al-Balqa Applied University (BAU) chosen randomly. The authors developed a study instrument which was divided into ambition level 10 items. Strong – Campbell Interest Inventory Scale was applied to examine the tendencies of vocational development. This scale consisted of 42 items divided into six domains.Results. The results showed there was a statistically significant positive relation between the ambition level and vocational tendency among BAU students. There were statistically significant differences at (.05 = a) in the ambition level attributed to the effect of the gender factor in favour of females. Also, there were statistically significant differences in the vocational tendencies attributed to the gender effect in all domains except the vocation selection domain. These differences were in favour of males in relation to the study materials domain, but in favour of females in relation to all the other domains as a whole. The vocational tendencies variable was considered a significant variable that increased the achievement of students’ ambitions.Scientific novelty. The study concluded that developing social changes require a high level of ambitions to cope with the continuous developments in different domains particularly the academic domain. Educators can develop students’ ambition level and identify vocational tendencies to excel in their own goals toward innovation and creativity in light of the common culture.Practical significance. The study draws interesting conclusions based on the analysis and discusses practical recommendations for key stakeholders. The Ministry of Education in Jordan should pay more attention to the vocational tendencies among students from earlier stages to direct these tendencies in appropriate ways that provide students with a good academic life leading to decent social, vocational and practical life that gets along with the common Jordanian culture. Besides, universities are recommended to focus on ways of developing the ambition level among students by raising parents’ awareness to set a good example to their children, bring them up from an early age to be ambitious and promote their ambition level.